Redox state of subcontinental lithospheric mantle and relationships with metasomatism: Insights from spinel peridotites from northern Victoria Land (Antarctica) - PERINELLI, cristina; ANDREOZZI, Giovanni Battista; Aida M. Conte; Roberta Oberti; Pietro Armienti (Contributions to Mineralogy and Petrology, 2012)
Rift-related Cenozoic alkaline mafic lavas from northern Victoria Land (Antarctica) carry abundant mantle xenoliths whose oxygen fugacities (fO2) were determined to assess how the metasomatism, related to Cenozoic magmatism, affected the state of oxidation of the lithospheric mantle. The xenoliths used for this study are anhydrous spinel peridotites sampled in two localities, Greene Point and Baker Rocks, that show different extents of metasomatism: these are limited to incompatible element enrichments in Greene Point and to enrichments in major, minor and trace elements at Baker Rocks. The data set includes a composite xenolith from Baker Rocks, formed by a depleted lherzolite crosscut by an amphibole-bearing vein. Mössbauer spectroscopy was used to accurately determine the Fe3+/Fetot ratios in spinel and amphibole minerals. Amphiboles were also characterized by Single-Crystal X-ray Diffraction, and the crystallographic data were used to calculate the dehydrogenation. The oxidation state recorded by the xenoliths ranges from 0. 2 to 1. 5 log-bar units below the fayalite-magnetite-quartz (FMQ) buffer (ΔlogfO2) with the highest values observed in the metasomatized samples from Greene Point. For the vein of composite Baker Rocks xenolith, Δlog fO2 was estimated on the basis of the amphibole in -1. 7 log-bar units, a value close to those calculated for all Baker Rocks xenoliths (ΔlogfO2 = -1. 5 to -1. 1 log-bar units). These results indicate a similar oxidation state for lithospheric mantle prior to the metasomatic event at Greene Point and Baker Rocks (ΔlogfO2 ~ -1. 3 log-bar units). Metasomatism produced different effects in the shallow mantle at the two sites. At Greene Point, an oxidizing metasomatic melt caused the rise of fO2 in peridotite portions close to melt conduits up to FMQ. In contrast, at Baker Rocks, a metasomatizing melt with fO2 similar to that of the peridotite matrix produced chemical changes in the surrounding mantle rocks and amphibole crystallization without significantly modifying the local ...